Convective Influence on the Humidity and Clouds in the Tropical Tropopause Layer During Boreal Summer. Issue 14 (17th July 2018) - Ueyama, Rei; Jensen, Eric J.; Pfister, Leonhard
Abstract: The impact of convection on the humidity and clouds in the tropical tropopause layer (TTL) during boreal summer 2007 is investigated in simulations of detailed cloud microphysical processes and their effects on the water vapor (H2 O) profile along backward trajectories from the 379 K potential temperature (100‐hPa pressure) surface. Convective influence is determined by tracing the trajectories through time‐dependent fields of satellite‐based convective cloud top height. The simulated H2 O mixing ratios at the 100‐hPa level and cloud occurrence fractions in the middle to upper (16–18 km) TTL exhibit a pronounced maximum over the Asian monsoon region as in observations; these local enhancements are virtually absent in the simulation without convection, indicating that convection is the dominant driver of the localized H2 O and cloud maxima in the Asian summer monsoon region. Convection moistens the 100‐hPa level by 0.6 ppmv (~15%) averaged over the 10°S–50°N domain and increases tropical (10°S–30°N) mean cloud occurrence in the middle to upper TTL by ~170%. Nearly all of the convective enhancements in H2 O and clouds are due to the effect of convective saturation; convectively detrained ice crystals have negligible impact. Parcels are most frequently hydrated by deep convection in the southern sector of the Asian monsoon anticyclone and subsequently dehydrated downstream of convection to the west, shifting the locations of final dehydration northwest of the cold temperature region in the northern Tropics. Infrequent, extreme deep convective systems (cloud tops exceeding 380 K) have a disproportionately large effect on TTL humidity and clouds. Key Points: Convection moistens (0.6 ppmv) and increases clouds (170%) in the summer TTL Convection is important for H2 O and cloud maxima over the Asian monsoon Convective ice has negligible impact on TTL humidity and clouds in summer